2016
DOI: 10.1111/bcp.13078
|View full text |Cite
|
Sign up to set email alerts
|

Pimasertib, a selective oral MEK1/2 inhibitor: absolute bioavailability, mass balance, elimination route, and metabolite profile in cancer patients

Abstract: Keywords14 C, absolute bioavailability, elimination route, mass balance, pimasertib AIMThis trial (NCT: 01713036) investigated the absolute bioavailability, mass balance and metabolite profile of pimasertib in a new design combining these investigations in a single group of patients. METHODSSix male patients with pathologically confirmed, locally advanced or metastatic solid tumours were enrolled. Exclusion criteria included Eastern Cooperative Oncology Group performance status >1. In Part A of the trial, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…elimination pathways and metabolites of drugs in vivo, are basic trials to characterize the pharmacokinetics (PK) of drugs and, therefore, are also recommended by such guidelines as the US Food and Drug Administration Guidance for Industry, Safety Testing of Drug Metabolites (Center for Drug Evaluation and Research, 2008), the International Conference on Harmonisation (ICH), Non-Clinical Safety Studies for the Conduct of Human Clinical Trials for Pharmaceuticals (International Conference on Harmonisation, 2009), and the European Medicines Agency's Guideline on the Investigation of Drug Interactions (European Medicines Agency, 2012). Final mass balance and total radioactivity data as well as early clinical findings have been reported previously from the human mass balance phase I study (NCT 01713036) that investigated the metabolic profile, mass balance, and oral bioavailability of pimasertib in patients with locally advanced or metastatic solid tumors (von Richter et al, 2016). In the current report, we describe in more detail the biotransformation of pimasertib following a single oral dose in the phase I study, and identify the metabolic profile of pimasertib in patients with advanced cancers.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…elimination pathways and metabolites of drugs in vivo, are basic trials to characterize the pharmacokinetics (PK) of drugs and, therefore, are also recommended by such guidelines as the US Food and Drug Administration Guidance for Industry, Safety Testing of Drug Metabolites (Center for Drug Evaluation and Research, 2008), the International Conference on Harmonisation (ICH), Non-Clinical Safety Studies for the Conduct of Human Clinical Trials for Pharmaceuticals (International Conference on Harmonisation, 2009), and the European Medicines Agency's Guideline on the Investigation of Drug Interactions (European Medicines Agency, 2012). Final mass balance and total radioactivity data as well as early clinical findings have been reported previously from the human mass balance phase I study (NCT 01713036) that investigated the metabolic profile, mass balance, and oral bioavailability of pimasertib in patients with locally advanced or metastatic solid tumors (von Richter et al, 2016). In the current report, we describe in more detail the biotransformation of pimasertib following a single oral dose in the phase I study, and identify the metabolic profile of pimasertib in patients with advanced cancers.…”
Section: Introductionmentioning
confidence: 73%
“…An open-label, single-center trial conducted in six male patients [age 18-65 years; Eastern Cooperative Oncology Group (ECOG) performance status #1] with locally advanced or metastatic solid tumors [defined by Response Evaluation Criteria In Solid Tumors (RECIST) v1.1] was performed. Full details of the patients, study design, dosing, and execution of the clinical part of this phase I study have previously been reported (von Richter et al, 2016). This report provides details of the identification of [ 14 C]-pimasertib metabolites in biologic samples taken from these patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a tracer IV dose reduces formulation work and, in line with ICH M3(R2) [31], may also not require generation of additional preclinical IV data to cover administration in humans. To optimize the approach, both investigations can even be performed in the same group of participants [32]. However, this approach was not applied in this study, due to practical considerations related to uncertainties regarding the duration of the excreta collection periods in part A of the study, which turned out to be shorter than initially expected.…”
Section: Discussionmentioning
confidence: 99%
“…This compound stabilizes p53 and activates its pathway, resulting in the interruption of the cell proliferation, cell cycle arrest and apoptosis, and is currently in phase I clinical trials for cancer treatment [122][123][124][125]. Another clinical trial was initiated with cancer patients involving safety and efficacy of MI-77301 [126] and Pimasertib (AS-703026), which is a highly selective, potent, ATP non-competitive allosteric inhibitor of MEK1/2 [127].…”
Section: Spiro-oxindole Indole and Carbazole Derivativesmentioning
confidence: 99%